In-kind transfers and household food consumption: implications for targeted food programs in Bangladesh - del Ninno, Carlo; Dorosh, Paul A. (International Food Policy Research Institute, 2002)
This paper examines the impact of wheat transfers and cash incomes on wheat consumption and wheat markets. Using propensity score- matching techniques, the total marginal propensity to consume (MPC) for wheat is, on average, 0.33, ranging from essentially zero for Food For Work (a program with large transfers) to 0.51 for Food For Education. Econometric estimates indicate that the MPC for small wheat transfers to poor households is approximately 0.25, while the MPC for wheat out of cash income is near zero. This increase in demand for wheat reduces the potential price effect of three major targeted programs involving small rations (Food For Education, Vulnerable Group Development, and Vulnerable Group Feeding) by about one-third.